Construction and characterization of a reovirus double temperature-sensitive mutant - Roner, Michael R. (The National Academy of Sciences of the USA, 1997)
The infectious reovirus RNA system was used to construct a mutant with two temperature-sensitive (ts) lesions in genome segments M2 and S2, respectively. The double mutant is about 300 times more ts than either of its parents, which are about 1,500 and 170 times more ts than their wild-type parent reovirus ST3 strain Dearing. At 39°C the double mutant is essentially unable to multiply. In spite of its striking temperature sensitivity, the double mutant elicits the formation of significant amounts of neutralizing antibodies in newborn mice. Possible mechanisms responsible for this are discussed, as is the significance of this double ts mutant in relation to current searches for safe and efficient vaccine strains.